Therapist-guided, Internet-based cognitive–behavioural therapy for body dysmorphic disorder (BDD-NET): a feasibility study. Issue 9 (25th September 2014) - Enander, Jesper; Ivanov, Volen Z; Andersson, Erik; Mataix-Cols, David; Ljótsson, Brjánn; Rück, Christian
Abstract : Objectives: Cognitive–behavioural therapy (CBT) is an effective treatment for body dysmorphic disorder (BDD). However, most sufferers do not have access to this treatment. One way to increase access to CBT is to administer treatment remotely via the Internet. This study piloted a novel therapist-supported, Internet-based CBT program for BDD (BDD-NET). Design: Uncontrolled clinical trial. Participants: Patients (N=23) were recruited through self-referral and assessed face to face at a clinic specialising in obsessive–compulsive and related disorders. Suitable patients were offered secure access to BDD-NET. Intervention: BDD-NET is a 12-week treatment program based on current psychological models of BDD that includes psychoeducation, functional analysis, cognitive restructuring, exposure and response prevention, and relapse prevention modules. A dedicated therapist provides active guidance and feedback throughout the entire process. Main outcome measure: The clinician-administered Yale-Brown Obsessive Compulsive Scale for BDD (BDD-YBOCS). Symptom severity was assessed pretreatment, post-treatment and at the 3-month follow-up. Results: BDD-NET was deemed highly acceptable by patients and led to significant improvements on the BDD-YBOCS (p=<0.001) with a large within-group effect size (Cohen's d=2.01, 95% CI 1.05 to 2.97). At post-treatment, 82% of the patients were classified as responders (defined as≥30% improvement on the BDD-YBOCS). These gains were maintained at the 3-month follow-up. Secondary outcome measures of depression, global functioning and quality of life also showed significant improvements with moderate to large effect sizes. On average, therapists spent 10 min per patient per week providing support. Conclusions: The results suggest that BDD-NET has the potential to greatly increase access to CBT, at least for low-risk individuals with moderately severe BDD symptoms and reasonably good insight. A randomised controlled trial of BDD-NET is warranted. Trial registration number: Clinicaltrials.gov registration ID NCT01850433 .